In : a graphic novel - McPhail, Will (Houghton Mifflin Harcourt, 2021)
"Nick, a young illustrator, can't connect with people. Whether it's the barista down the street, his own family, or Wren, an oncologist whose life becomes painfully tangled with his, Nick can't shake the feeling that there is some hidden realm of human interaction beyond his reach. He staggers through meaningless conversations and haunts lookalike vacuous coffee shops in the hope that he will find it there. But it isn't until Nick learns to stop performing and speak about the things that really matter that the complex and colorful worlds of the people he meets are finally revealed to him."--Back cover.